The impact of creditor protection on stock prices in the presence of credit crunches - Galina Hale; Assaf Razîn; Hui Tong (Center for Economic Studies and ifo Institute (CESifo), 2011)
Data show that better creditor protection is correlated across countries with lower average stock market volatility. Moreover, countries with better creditor protection seem to have suffered lower decline in their stock market indexes during the current financial crisis. To explain this regularity, we use a Tobin q model of investment and show that stronger creditor protection increases the expected level and lowers the variance of stock prices in the presence of credit crunches. There are two main channels through which creditor protection enhances the performance of the stock market: (1) The credit-constrained stock price increases with better protection of creditors; (2) The probability of a credit crunch leading to a binding credit constraint falls with strong protection of creditors. We find strong empirical support for both predictions using data on stock market performance, amount and cost of credit, and creditor rights protection for 52 countries over the period 1980-2007. In particular, we find that crises are more frequent in countries with poor creditor protection. Using propensity score matching we also show that during crises stock market returns fall by more in countries with poor creditor protection.
Keywords: E44; 330; liquidity crisis; creditor protection; stock volatility; credit crunch; Gläubigerschutz; Aktienmarkt; Börsenkurs; Volatilität; Tobin's Q; Finanzmarktkrise; OECD-Staaten